2019
DOI: 10.1177/0748730419847845
|View full text |Cite
|
Sign up to set email alerts
|

Living in Biological Darkness: Objective Sleepiness and the Pupillary Light Responses Are Affected by Different Metameric Lighting Conditions during Daytime

Abstract: Nighttime melatonin suppression is the most commonly used method to indirectly quantify acute nonvisual light effects. Since light is the principal zeitgeber in humans, there is a need to assess its strength during daytime as well. This is especially important since humans evolved under natural daylight but now often spend their time indoors under artificial light, resulting in a different quality and quantity of light. We tested whether the pupillary light response (PLR) could be used as a marker for nonvisua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 88 publications
0
32
2
Order By: Relevance
“…This variation may be due to individual subjects state of arousal; studies have suggested that a correlation exists between the PIPR and subjective sleepiness, such that the PIPR is smaller when subjects are sleepier. 49 Although we did not measure sleepiness, it is possible that exposure to 1 hour of darkness increased subjects’ sleepiness. Because we did not observe a significant difference in the 6-second PIPR after 1 hour of dark exposure, our results suggest that 5 minutes of dark adaptation should be sufficient to obtain a stable PIPR response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This variation may be due to individual subjects state of arousal; studies have suggested that a correlation exists between the PIPR and subjective sleepiness, such that the PIPR is smaller when subjects are sleepier. 49 Although we did not measure sleepiness, it is possible that exposure to 1 hour of darkness increased subjects’ sleepiness. Because we did not observe a significant difference in the 6-second PIPR after 1 hour of dark exposure, our results suggest that 5 minutes of dark adaptation should be sufficient to obtain a stable PIPR response.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with previous studies demonstrating the effects of light- and dark-adapted conditions on pupil constriction. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…The direction of light seems to be crucial at least for electric light that was shown to affect melatonin suppression [107][108][109] and sleep [110]. From laboratory studies with electric lighting interventions during the daytime, mixed dose-response effects have been reported for intensity, duration and spectral composition: Some studies found effects of daytime/evening electric light exposure on subjective and/or objective variables [52,86,89,115], while others did not [82,116]. Few studies have been conducted under daylight conditions only or mixed daylight/electric light conditions, and most of these are applied or semi-natural studies [40,65,78].…”
Section: Role Of Light Distribution In the Visual Field Direction Ofmentioning
confidence: 99%
“…Many laboratory studies with steady state electric lighting showed light-dependent alertness[45,46,49,[81][82][83] and cognitive repercussions[46,53,55]. A few studies have looked at spectrally tuned electrical light conditions and alertness and cognition[76,[84][85][86].…”
mentioning
confidence: 99%
“…In recent years however, the effects of artificial light, in addition to natural sunlight, have gained increasing interest, particularly with the advent of light-emitting diodes (LEDs; see e.g., Blume, Garbazza, and Spitschan [20]) whose light spectrum is "circadian active". Moreover, natural daylight plays a decreasing role in modern societies, with some authors even arguing that many people live in "biological darkness" [21]. In the DST/ST debate, this is a crunch point as it relates to the question of how much the body clock depends on the apex of the sun's motion coinciding with 12 pm/noon in a world with an increasingly complex light environment.…”
Section: Importance Of the Solar Clock And Artificial Lightmentioning
confidence: 99%